2010
DOI: 10.3844/ajassp.2010.265.269
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Stock Market Performance and Economic Growth

Abstract: Problem statement:In spite of significant development in Iran stock market as a emerging stock market, there has been not specific research on the causality between the stock prices and economic growth. This study represented a systematic investigation of the relationship between stock market performance and economic growth in Iran by conducting causality tests within the Vector Error Correction Model (VECM) framework. Approach: To achieve this objective unit root tests are fulfilled for all time series data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…The increasing trends of market capitalization in India would certainly bring about efficiency in capital market and thereby contribute to economic growth. Oskooe (2010) assessed the relationship between stock market performance and economic growth in Iran by using causality tests within a Vector Error Correction Model (VECM) structure. Quarterly time series data was used from the third quarter of 1997 to the third quarter of 2008.…”
Section: IImentioning
confidence: 99%
“…The increasing trends of market capitalization in India would certainly bring about efficiency in capital market and thereby contribute to economic growth. Oskooe (2010) assessed the relationship between stock market performance and economic growth in Iran by using causality tests within a Vector Error Correction Model (VECM) structure. Quarterly time series data was used from the third quarter of 1997 to the third quarter of 2008.…”
Section: IImentioning
confidence: 99%
“…Victors stated that establishment of Ghana Stock Exchange (GSE) has positive impact on economic growth in Ghana since it became operational. Oskooe (2010) stated that stock market acts as a leading indicator market development in Iran. Shahbaz et al (2012) indicated that stock market development is an important wheel for economic growth in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Levine and Zervos (1996) discovered a strong empirical relationship linking long-run economic growth to stock market development. Seyyed (2010) presented a systematic investigation of the relationship between stock markets performance and economic growth using the Vector Autoregressive (VAR) model and found that macroeconomic activity significantly explained the movement of stock prices in the long run. Nurudeen (2009) found results indicating that stock market development increased economic growth in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%